Identifieringen av Olavsaltaren i Finland som metodologiskt problem - Knuutila, Jyrki (Hikuin, 2006)
Identification of Altars of St. Olav in Finland as a methodological problem By Jyrki Knuutila The cult of the patron saint of Norway, St. Olav has been one of the most important saint cults during the Middle Ages in Finland, as well. There are many evidences of that he has been worshipped both by ecclesiastical and popular adoration. Therefore, many Altars of St. Olav should be supposed to exist in Finland. However, there you can’t find almost any evidences of mentioned Altars, neither literally nor archaeological. The only obvious literally evidences come from 17th Century, not also from the Middle Ages. Despite of this exiguity of evidences, Altars of St. Olav can be supposed to have existed because of popularity of his cult. In this study, existence of named Altar has been investigated by considering evidences concerning the cult of St. Olav. Those evidences have been studied methodically of viewpoint of Altars of St. Olav. The Finnish medieval churches have had main altars and side altars, as well. Number of the last mentioned altars has been different in various churches. According to Canon law, bishops should consecrate Altars. However, you can ask if all side altars in Finland have had an Episcopal consecration. They could have had benediction of local priest, as well. Some side altars could not have been consecrated or blessed, at all. Thus, the concept of altars dedicated to St. Olav has been used in this study instead of concept of altars consecrated or blessed to him. According to common source-material concerning dedication of altars in Finnish medieval churches, both main and side altars dedicated to St. Olav seems to exist in churches consecrated to him. However, main altars have not automatically been dedicated to St. Olav in churches consecrated to him. There are some churches where the cult of St. Olav has been very important according indulgence letters, liturgical material connected with his cult and sculptures in the altarscreen of St. Olav and some freestanding sculptures evidenced historical records. Altars dedicated to him can be assumed to exist in those churches because liturgical cult of a Saint has been linked to an altar. As well, there are some other concrete circular evidences linked to the cult of St. Olav in some churches. Those churches could also have had altars dedicated to him. The number of churches with Altars of St. Olav varies between 10 and 39. The number is depending on how many evidences do exist per church and how to interpret the weight as evidence of each one of evidences.